2017
DOI: 10.1167/iovs.16-20866
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Bovine and Human Ciliary Zonule

Abstract: PurposeThe zonule of Zinn (ciliary zonule) is a system of fibers that centers the crystalline lens on the optical axis of the eye. Mutations in zonule components underlie syndromic conditions associated with a broad range of ocular pathologies, including microspherophakia and ectopia lentis. Here, we used HPLC–mass spectrometry to determine the molecular composition of the zonule.MethodsTryptic digests of human and bovine zonular samples were analyzed by HPLC–mass spectrometry. The distribution of selected com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 61 publications
5
73
1
1
Order By: Relevance
“…This result confirmed our earlier proteomic analysis of microfibrils purified from zonules, aorta and skin, which had detected only the fibrillin-1 isoform in human zonules, alongside low levels of the microfibril-associated glycoprotein MAGP-1 (see 'Microfibril-associated molecules') (Cain et al 2006). A recent proteomic analysis (De Maria et al 2017) confirmed that fibrillin-1 and MAGP-1, with LTBP-2, are the most abundant components of human zonules.…”
Section: Fibrillinssupporting
confidence: 87%
See 2 more Smart Citations
“…This result confirmed our earlier proteomic analysis of microfibrils purified from zonules, aorta and skin, which had detected only the fibrillin-1 isoform in human zonules, alongside low levels of the microfibril-associated glycoprotein MAGP-1 (see 'Microfibril-associated molecules') (Cain et al 2006). A recent proteomic analysis (De Maria et al 2017) confirmed that fibrillin-1 and MAGP-1, with LTBP-2, are the most abundant components of human zonules.…”
Section: Fibrillinssupporting
confidence: 87%
“…A recent proteomic analysis (De Maria et al . ) confirmed that fibrillin‐1 and MAGP‐1, with LTBP‐2, are the most abundant components of human zonules.…”
Section: The Fibrillin Superfamilymentioning
confidence: 60%
See 1 more Smart Citation
“…The zonule serves to suspend the lens in the eye (see Figure 7A). Recent proteomic analysis of the human and bovine zonule has shown that Fibrillin 1 and LTBP2 (genes implicated in WMS-2, WMS-3, MSPKA, and GPHYSD-2) are the two most abundant components (de Maria et al, 2017). Neither is strongly expressed in the lens, however (Shi et al, 2013).…”
Section: Molecular Genetic Insights Into Lens Growth Regulationmentioning
confidence: 99%
“…Neither is strongly expressed in the lens, however (Shi et al, 2013). Similarly, ADAMTSL2 has been detected in the zonule and to a lesser degree in the vitreous humor (de Maria et al, 2017). These clinical observations raise the possibility that the zonule, which constitutes the mechanical linkage between the lens and the wall of the eye, may actively modulate lens growth.…”
Section: Molecular Genetic Insights Into Lens Growth Regulationmentioning
confidence: 99%